Industrial Engineering and Operations Management – a view from IJCIEOM 2020-2021 - Thomé, Antonio Márcio Tavares; Barbastefano, Rafael; Reis, João Carlos Gonçalves dos; Scavarda, Luiz Felipe; Freires, Francisco Gaudêncio Mendonça (Brazilian Journal of Operations & Production Management, 2021)
This Special Issue of the Brazilian Journal of Operations and Production Management (BJOPM) offers nine papers selected from the 26th International Joint Conference on Industrial Engineering and Operations Management (IJCIEOM – 2020-2021). The conference theme was “Challenges and Trends for Sustainability in the 21st Century”, looking ahead to bridge theory and practice of economic, social, and environmental sustainability. This editorial paper summarises the selected contributions of collaborative efforts of international researchers to advance knowledge in different research topics of industrial engineering and operations management.